Suprapubic Hot Pack For Recovery of Urinary Vesical Reflexes on Post Spinal Anaesthesia Patients - Aprina, Aprina; Suwoyo, Nadiyah (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2024)
Urinary retention after spinal anaesthesia and surgery ranges from 5%-70%, with men and the elderly at higher risk. This occurs because the urethral sphincter muscle does not respond to the urge to urinate and the patient is unable to feel the need to urinate. One treatment for this problem is providing hot pack media as a warm therapy in the suprapubic area. The purpose of this study was to determine the effect of suprapubic hot pack therapy on the recovery of post spinal anaesthesia vesical urinary reflex. This quantitative study uses a quasy experiment design with a static group comparison approach. The population of this study was postoperative patients with spinal anaesthesia. The sample size was 60 respondents with accidental sampling. The research design has treatment and control groups, then measuring the results with observation sheets. Using the independent t-test for the analisys. The result showed the average recovery time of vesica urine was 225.5 minutes for intervention group and 295 minutes for control group with a p-value (0.000) < Î± (0.05), which means that there is an effect of suprapubic hot pack therapy on the recovery of vesica urine reflexes after spinal anaesthesia. Based on the results of this research, this procedure is an effective nursing intervention that can be applied in surgical inpatient rooms for the care of post-operative patients, especially in patients with spinal anaesthesia to speed up the recovery of the patient's bladder reflex.